Pengaruh Intervensi Nonfarmakologi Dan Farmakologi Terhadap Penurunan Intensitas Nyeri Pada Pasien Penyakit Jantung Koroner Di Ruang ICCU RSU Kota Langsa Tahun 2012 - Sunarsih Rahayu; Amrin Amrin ((JKG) Jurnal Keperawatan Global, 2016)
Abstract : Intervention Of Nonpharmacological And Pharmacological, Coronary Heart Disease, Pain Intensity. Chest pain in the cardiovascular system is one of the main complaints which often complained patients to ask for medical help. The pain is different from one individual to another based on the pain threshold and tolerance release of endorphins enkefalin which incurred hifofisis into the circulation. The chest pain which felt by the patients tend to require more urgent attention than the other symptoms. Objectives of the study was to determine the intervention effect of pharmacologi and nonpharmacologi to pain intensity decrease in coronary heart disease patients. This type of research was experimental, research design using quasi experiment. Sampling using total of sampling method. Analysis of data used was t dependent test. Results was show that there was a significant effect between intensity of pain before intervention to the intensity of pain after intervention. Conclusion, Intervention of nonpharmacologi and pharmacologi provide a positive and significant effect on pain intensity decrease.